BioScript: Programming Safe Chemistry on Laboratories-on-a-Chip. - Ott, Jason; Loveless, Tyson; Curtis, Chris; Lesani, Mohsen; Brisk, Philip (Communications of the ACM, 2021)
This paper introduces BioScript, a domain-specific language (DSL) for programmable biochemistry that executes on emerging microfluidic platforms. The goal of this research is to provide a simple, intuitive, and type-safe DSL that is accessible to life science practitioners. The novel feature of the language is its syntax, which aims to optimize human readability; the technical contribution of the paper is the BioScript type system. The type system ensures that certain types of errors, specific to biochemistry, do not occur, such as the interaction of chemicals that may be unsafe. Results are obtained using a custom-built compiler that implements the BioScript language and type system.